Exploration of waste-generated nanocomposites as energy-driven systems for various methods of hydrogen production; A review. (30th April 2022) - Mohamed Jan, Badrul; Bin Dahari, Mahidzal; Abro, Mehwish; Ikram, Rabia
Abstract: Recently, waste-generated nanomaterials have received a surge in consideration for energy production due to their excellent properties and eco-friendly effects. A plethora of literature has reported on the growing interest for the production of hydrogen (H2 ) by utilizing sunlight through water splitting and the recycling of bio-waste into organic catalysts. To the best of our knowledge, there has been no review on waste-derived nanocomposites for the production of H2 . Herein, potential methods, modes of fabrication, and the efficacy of synthesized nanocomposites for H2 production have been highlighted. Distinct attention has been given to waste-generated nanocomposites, including a variety of graphene nanomaterials. Remarkable efforts have been made to fabricate biomass-derived nanomaterials and to optimize their reaction conditions and efficient use in energy production. Finally, future prospects and challenges in improving photocatalytic H2 production are also summarized. Graphical abstract: Image 1 Highlights: An overview of carbon materials including graphene nanocomposites for H2  production is abridged. Numerous remarkable methods for H2  production are highlighted. Efficacy of waste-derived nanocomposites for H2  production are provided through various methods. Strategies to advance the photocatalytic H2  and other energy production are summarized.